Assessing thrombogenesis and treatment response in congenital thrombotic thrombocytopenic purpura. Issue 2 (28th February 2021) - Alwan, Ferras; Vendramin, Chiara; Budde, Ulrich; Liesner, Ri; Taylor, Alice; Thomas, Mari; Lämmle, Bernhard; Scully, Marie
Abstract: Despite clinical remission and normal platelet counts, congenital TTP (cTTP) is associated with non‐overt symptoms. Prophylactic ADAMTS13 replacement therapy such as plasma infusion (PI) prevents acute episodes and improves symptomatology. There is no current method to investigate disease severity or monitor the impact of treatment. We utilize a dynamic high shear flow assay to further understand disease pathophysiology and determine the impact of cTTP on symptomatology and therapy, despite normal platelet counts. Whole blood, under high shear, was run over collagen‐coated channels, causing platelet adhesion to von Willebrand factor (VWF) multimers. The resulting surface coverage by platelet‐VWF thrombus was assessed. The normal range was 6–39% in 50 controls. Twenty‐two cTTP patients with normal platelet counts were evaluated. Median pre‐treatment surface coverage was 89%, and PI reduced coverage to a median of 44% ( p = 0.0005). Patients taking antiplatelets had further reduced coverage when combined with PI and improved non‐overt symptoms such as headache, lethargy, and abdominal pain in 100% of patients compared to 74% with PI alone ( p = 0.046). We use a dynamic assay to report increased in vitro platelet adhesion and aggregation and additionally demonstrate significantly decreased thrombi following PI, with levels in the normal range levels achieved in patients taking additional antiplatelet therapy.